Proton Conductive Materials
Patent Information
- Application Number
- JP2021127876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-04
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-08-04
AI Technical Summary
【0012】 本開示によれば、無加湿下でも高いプロトン伝導率を有し、水に対し溶出しないプロトン伝導材料を提供することができる。
Smart Images

Figure 0007636291000008 
Figure 0007636291000001 
Figure 0007636291000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to proton conducting materials that can be used in solid electrolyte membranes and the like used in fuel cells. [Background technology]
[0002] Conventionally, perfluorosulfonic acid resin membranes such as Nafion (registered trademark, the same applies below) have been used as solid electrolyte membranes for fuel cells. However, in order to achieve high proton conductivity with perfluorosulfonic acid resin membranes, the presence of water is essential, and therefore they must be used at temperatures below the boiling point of water (100°C). For this reason, conventional fuel cells using perfluorosulfonic acid resin membranes are equipped with humidification systems and temperature control systems to ensure an appropriate amount of moisture, which causes problems such as the increase in size and cost of fuel cell devices.
[0003] In view of these circumstances, in recent years, attempts have been made to develop proton-conducting materials that can be used in the absence of humidity. For example, Patent Document 1 discloses an electrolyte membrane that contains a strong acid such as phosphoric acid and a basic polymer such as polybenzimidazole as a solid electrolyte membrane that can be used in the absence of humidity. Furthermore, Patent Document 2 discloses a proton conductive membrane that contains a block copolymer having A blocks that aggregate with each other to form domains at a usage temperature and B blocks that have proton-accepting groups, in which the B blocks bridge the domains, and a plasticizer that is a low-volatility acidic substance.
[0004] On the other hand, an ion conductor composed of an inorganic porous membrane and an ionic liquid held in the inorganic porous membrane, as described in Patent Document 3, is also known as an electrolyte membrane that can be used in the absence of humidification. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-32275 A [Patent Document 2] JP 2020-68130 A [Patent Document 3] JP 2007-311311 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, when the electrolyte membranes disclosed in Patent Documents 1 to 3 are used in fuel cells, the generated water causes acid or ionic liquid to dissolve from the electrolyte membrane, which causes the operation of the fuel cell to become unstable and the power generation performance to easily decrease.
[0007] The present disclosure has been made in consideration of the above circumstances, and has as its main object to provide a proton-conducting material that has high proton conductivity even in an unhumidified state and does not dissolve in water. [Means for solving the problem]
[0008] A proton conducting material according to a first embodiment of the present disclosure contains a polymer containing a proton source group and a polymer containing a proton channel, and is characterized in that at least one selected from the group consisting of the polymer containing the proton source group and the polymer containing the proton channel is a polymer containing an aromatic ring, and at least a portion of the polymer containing an aromatic ring has a structure stacked by π-π interactions.
[0009] In the proton conducting material according to the first embodiment of the present disclosure, the polymer containing a proton source group may contain at least one selected from a styrenesulfonic acid-based polymer and a perfluorosulfonic acid-based polymer.
[0010] In the proton conducting material according to the first embodiment of the present disclosure, the polymer having the proton channel may contain a polymer having at least one group selected from the group consisting of a pyridyl group, a phenanthroline group, and a diazadibenzofulvene group. In the proton conducting material according to the first embodiment of the present disclosure, the polymer containing the proton channel may further contain polyethylene oxide.
[0011] A proton conducting material according to a second embodiment of the present disclosure contains a polymer including a proton source group and a proton channel, the polymer including the proton source group and the proton channel being a polymer having a main skeleton including a proton source group and an aromatic ring and a cross-linked structure including a proton channel, and at least a portion of the polymer including the proton source group and the proton channel having a structure stacked by π-π interactions. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a proton-conducting material that has high proton conductivity even in an unhumidified state and does not dissolve in water. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a graph showing the proton conductivity at each temperature for the proton conductive membrane of Example 18 and the comparative conductive membrane of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] A proton conducting material according to a first embodiment of the present disclosure contains a polymer containing a proton source group and a polymer containing a proton channel, and is characterized in that at least one selected from the group consisting of the polymer containing the proton source group and the polymer containing the proton channel is a polymer containing an aromatic ring, and at least a portion of the polymer containing an aromatic ring has a structure stacked by π-π interactions. In the first embodiment of the present disclosure, a polymer containing the proton source group may be referred to as a "proton source polymer", and a polymer containing the proton channel may be referred to as a "proton channel polymer".
[0015] A proton conducting material according to a second embodiment of the present disclosure contains a polymer including a proton source group and a proton channel, the polymer including the proton source group and the proton channel being a polymer having a main skeleton including a proton source group and an aromatic ring and a cross-linked structure including a proton channel, and at least a portion of the polymer including the proton source group and the proton channel having a structure stacked by π-π interactions. In the second embodiment of the present disclosure, the polymer including the proton source group and the proton channel may be referred to as a "proton source cross-linked polymer." Moreover, the proton conducting material according to the second embodiment of the present disclosure may further contain a polymer that does not contain a proton source group and that contains a proton channel. In the second embodiment of the present disclosure, a polymer that does not contain a proton source group and contains a proton channel may be referred to as a "proton channel polymer".
[0016] The proton conductive material of the present disclosure has high proton conductivity in the absence of humidification in both the first and second embodiments. The proton conductive material of the present disclosure includes a proton source group that releases protons and a proton channel that coordinates protons, and therefore exhibits proton conductivity even in the absence of humidification. In the above first embodiment, it is presumed that the polymer to which the proton source group or the proton channel is chemically bonded has a structure in which the polymer is stacked by π-π interactions, thereby forming a crystalline ordered structure through which protons can easily move, and that the polymer has a conformation that makes it easy for a proton conduction path to be formed between the proton source group and the proton channel, thereby providing high proton conductivity even in the absence of humidification. In the above second embodiment, a main skeleton including a proton source group and an aromatic ring, and a polymer having a cross-linked structure including a proton channel have a structure in which they are stacked through π-π interactions, forming a crystalline ordered structure through which protons can easily move, and it is presumed that the structure has a conformation that makes it easy for a proton conduction path to be formed between the proton source group in the main skeleton and the proton channel in the cross-linked structure, and therefore it is presumed that the material has high proton conductivity even in the absence of humidification. In both the first and second embodiments, the proton source group and the proton channel are chemically bonded to the polymer and do not dissolve in water, so the proton conductive material of the present disclosure does not contain any components that dissolve in water. When the proton conductive material of the present disclosure is used in a fuel cell or the like, the operation of the fuel cell is unlikely to become unstable because there is no dissolution of acids or the like into the generated water. In addition, although the electrolyte membranes disclosed in Patent Documents 1 to 3 can be used without humidification, the electrolyte membranes disclosed in Patent Documents 1 and 3 tend to have a decreased proton conductivity in the medium-low temperature range below 100° C., and the electrolyte membrane disclosed in Patent Document 2 is difficult to use in the high temperature range due to its low glass transition temperature. Therefore, when the electrolyte membranes disclosed in Patent Documents 1 to 3 are used, it is difficult to maintain high proton conductivity in a wide temperature range. In contrast, in a preferred embodiment of the proton conductive material of the present disclosure, it is possible to have high proton conductivity in a wide temperature range without humidification. Since the polymer structure is stable due to π-π interactions or crosslinking, and transition of the polymer structure due to temperature change is unlikely to occur, it is presumed that the material exhibits high proton conductivity in a wide temperature range without humidification. When a proton conductive membrane having high proton conductivity in a wide temperature range without humidification is used in a fuel cell, the humidification system and temperature control system introduced in the fuel cell device can be further simplified or eliminated, thereby realizing a revolutionary cost reduction in the fuel cell device.
[0017] In this disclosure, "unhumidified" refers to an environment with a humidity of 5% RH or less. In the present disclosure, the aromatic ring may be an aromatic hydrocarbon ring or an aromatic heterocycle. In addition, in the present disclosure, the use of "to" in a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Hereinafter, a first embodiment and a second embodiment of the proton-conducting material of the present disclosure will be described in detail.
[0018] First Embodiment A proton conducting material according to a first embodiment of the present disclosure contains a proton source polymer and a proton channel polymer, in which at least one selected from the group consisting of the proton source polymer and the proton channel polymer is a polymer containing an aromatic ring, and at least a portion of the polymer containing an aromatic ring has a structure stacked by π-π interactions. In a first embodiment of the present disclosure, the proton source polymer and the proton channel polymer are different polymers, and it is preferable that the proton source polymer does not contain a proton channel, and it is preferable that the proton channel polymer does not contain a proton source group.
[0019] (Proton Source Polymer) In the present disclosure, the proton source group is not particularly limited as long as it is a group capable of releasing a proton. Examples of the proton source group include a sulfo group (-SO 3 Examples of the proton source group include sulfo groups (-H), carboxy groups (-COOH), hydroxy groups (-OH), thiol groups (-SH), imidazole groups, and benzimidazole groups. Of these, the sulfo group is preferred from the viewpoint of improving proton conductivity. As the proton source group that is likely to form a layered structure by π-π interaction, for example, a proton source group containing an aromatic ring such as an imidazole group or a benzimidazole group is preferably used.
[0020] In order to improve the proton conductivity of the proton-conducting material, the proton source polymer may be a polymer composed of constituent units derived from a monomer containing a proton source group, and the content of constituent units derived from a monomer containing a proton source group is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, per 100 parts by mass of all constituent units.
[0021] The proton source polymer may be a hydrocarbon-based organic polymer or a perfluoro-based organic polymer. In the present disclosure, the hydrocarbon-based organic polymer may contain a heteroatom, and the perfluoro-based organic polymer may contain a heteroatom other than fluorine.
[0022] In the hydrocarbon-based proton source polymer, examples of the constituent units derived from a monomer containing a proton source group include constituent units derived from a monomer such as 4-styrenesulfonic acid, 4-vinylbenzoic acid, 2-vinylbenzoic acid, 4-vinylphenol, 2-vinylphenol, 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole, 4-(1H-imidazol-1-yl)styrene, 2-vinyl-1H-benzimidazole, 1-vinyl-1H-benzimidazole, and 4-(1H-benzo[d]imidazol-1-yl)styrene. In the present disclosure, the constituent units derived from styrenesulfonic acid also include those obtained by polymerizing salts such as sodium styrenesulfonate and then hydrogenating them.
[0023] As the hydrocarbon-based proton source polymer, a styrenesulfonic acid-based polymer is preferably used from the viewpoint of improving the proton conductivity of the proton-conducting material. In the present disclosure, the styrenesulfonic acid-based polymer means a polymer containing a constitutional unit derived from styrenesulfonic acid. The styrene sulfonic acid-based polymer may be a polystyrene sulfonic acid composed of structural units derived from styrene sulfonic acid, preferably having a content of structural units derived from styrene sulfonic acid of 90 parts by mass or more, more preferably 95 parts by mass or more, per 100 parts by mass of all structural units. In the case where the styrene sulfonic acid-based polymer contains a constituent unit derived from a monomer other than styrene sulfonic acid, examples of the other monomer include styrene, substituted styrene having a substituent other than a sulfo group, vinylfluorene, dibenzofulvene, and 4,5-diazabenzofulvene.
[0024] The number average molecular weight Mn of the styrene sulfonic acid polymer is not particularly limited, but is preferably 4000 to 10000, more preferably 5000 to 9000, and further preferably 6000 to 8000. When the number average molecular weight Mn of the styrene sulfonic acid polymer is within the above range, proton source groups are easily accumulated and proton conductive paths are easily generated, so that the proton conductivity of the proton conductive material is easily improved.
[0025] As a hydrocarbon-based proton source polymer that is likely to form a laminated structure by π-π interaction, for example, a hydrocarbon-based proton source polymer containing an aromatic ring is used. Among them, a polymer containing at least one constituent unit selected from the group consisting of vinylimidazole, 4-(1H-imidazol-1-yl)styrene, and vinylbenzimidazole is preferably used. In the polymer, the content of the constituent unit derived from vinylimidazole, 4-(1H-imidazol-1-yl)styrene, or vinylbenzimidazole is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and may be 100 parts by mass, out of 100 parts by mass of all constituent units. The number average molecular weight Mn of the aromatic ring-containing hydrocarbon proton source polymer is not particularly limited, but is preferably 1000 to 100,000.
[0026] The perfluoro-based proton source polymer is a polymer made of perfluorocarbon that contains a proton source group in the main chain or side chain and may further contain a heteroatom. From the viewpoint of improving the proton conductivity of the proton conductive material, the proton source group is preferably contained in the side chain. From the viewpoint of improving the proton conductivity of the proton conductive material, the perfluoro-based proton source polymer is preferably a perfluorosulfonic acid-based polymer containing a sulfo group, more preferably a perfluorosulfonic acid-based polymer containing a sulfo group in the side chain, and particularly preferably a perfluorosulfonic acid-based polymer having a main chain made of perfluoroalkylene and a side chain derived from perfluorovinyl ether substituted with a sulfo group. As the perfluorosulfonic acid-based polymer, for example, Nafion (registered trademark, manufactured by Dupont), Aquivion (registered trademark, manufactured by Solvay), etc. can be suitably used. Note that Nafion (registered trademark) is a copolymer of tetrafluoroethylene and perfluoro[2-(fluorosulfonylethoxy)propyl vinyl ether].
[0027] The proton source polymer preferably contains at least one selected from the styrene sulfonic acid polymer and the perfluorosulfonic acid polymer, since the proton conductivity of the proton-conducting material is likely to be improved. On the other hand, when the proton channel polymer contained in the proton conductive material does not contain an aromatic ring, the proton source polymer preferably contains a proton source polymer that is likely to form a layered structure due to π-π interactions, and in particular, it is preferable to contain a polymer containing a structural unit derived from at least one selected from the group consisting of vinylimidazole, 4-(1H-imidazol-1-yl)styrene, and vinylbenzimidazole.
[0028] (Proton channel polymer) In the present disclosure, the proton channel is not particularly limited as long as it has a structure capable of coordinating a proton. Examples of the structure that serves as a proton channel include a pyridyl group, a phenanthroline group, a diazadibenzofulvene group, a polyalkylene oxide group, a primary or secondary amino group, an amide group, and an amide bond. Among these, as a proton channel that is likely to form a layered structure through π-π interactions and that is likely to improve proton conductivity, at least one group selected from the group consisting of a pyridyl group, a phenanthroline group, and a diazadibenzofulvene group is preferred, and among these, at least one group selected from the group consisting of a 2-pyridyl group, a 1,10-phenanthroline group, and a 4,5-diazadibenzofulvene group is more preferred. In the present disclosure, the 1,10-phenanthroline group is a group represented by the following chemical formula (1), and the 4,5-diazadibenzofulvene group is a group represented by the following chemical formula (2). In the chemical formulas (1) and (2), * represents a bond.
[0029] [ka]
[0030] In order to improve the proton conductivity of the proton conductive material, the proton channel polymer may be a polymer composed of structural units derived from monomers containing proton channels, and the content of structural units derived from monomers containing proton channels is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, per 100 parts by mass of all structural units.
[0031] The proton channel polymer may be a hydrocarbon-based organic polymer. In the above-mentioned proton channel polymer, examples of the constituent units derived from a monomer containing a proton channel include constituent units derived from a monomer such as 2-vinylpyridine, 4-vinylpyridine, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate, as well as 1,10-phenanthroline and 4,5-diazadibenzofulvene.
[0032] As a proton channel polymer that is easy to form a laminated structure by π-π interaction and is easy to improve the proton conductivity of a proton conductive material, a proton channel polymer containing an aromatic ring is used, and among them, a polymer containing at least one type of constitutional unit selected from the group consisting of a constitutional unit derived from 2-vinylpyridine, 1,10-phenanthroline, and 4,5-diazadibenzofulvene is preferably used. Among them, at least one type selected from the group consisting of poly(2-vinylpyridine), poly(1,10-phenanthroline), and poly(4,5-diazadibenzofulvene) is preferable. Here, the content of the constitutional unit derived from 2-vinylpyridine, 1,10-phenanthroline, and 4,5-diazadibenzofulvene in poly(2-vinylpyridine), poly(1,10-phenanthroline), and poly(4,5-diazadibenzofulvene) may be 90 parts by mass or more, more preferably 95 parts by mass or more, and may be 100 parts by mass, in 100 parts by mass of all constitutional units. When poly(2-vinylpyridine), poly(1,10-phenanthroline) and poly(4,5-diazadibenzofulvene) contain structural units derived from other monomers, examples of the other monomers include styrene, substituted styrene, vinylfluorene, dibenzofulvene, and 4,5-diazabenzofulvene. Poly(1,10-phenanthroline) containing no other structural units is a polymer represented by the following chemical formula (1'), and poly(4,5-diazadibenzofulvene) containing no other structural units is a polymer represented by the following chemical formula (2').
[0033] [ka]
[0034] The number average molecular weight Mn of poly(2-vinylpyridine) is not particularly limited, but is preferably 300 to 3000, more preferably 400 to 2500, and further preferably 500 to 2000. When the number average molecular weight Mn of poly(2-vinylpyridine) is within the above range, 2-pyridyl groups are easily accumulated by π-π interactions, and proton conductive paths are easily generated, so that the proton conductivity of the proton conductive material is easily improved.
[0035] The number average molecular weight Mn of poly(1,10-phenanthroline) is not particularly limited, but when the above-mentioned styrene sulfonic acid polymer is used as the proton source polymer, it is preferably 700 to 1500, more preferably 800 to 1300, even more preferably 900 to 1100, and particularly preferably 1000. On the other hand, when the above-mentioned perfluorosulfonic acid polymer is used as the proton source polymer, it is preferably 7000 to 15000, more preferably 8000 to 13000, even more preferably 9000 to 11000, and particularly preferably 10000. When the number average molecular weight Mn of poly(1,10-phenanthroline) is within the above range, 1,10-phenanthroline groups are easily accumulated by π-π interaction, and a proton conduction path is easily generated, so that the proton conductivity of the proton conductive material is easily improved. Poly(1,10-phenanthroline) can be synthesized, for example, by referring to W. Yang and T. Nakano, Chem. Commun., 2015, 51, p. 17269-17272.
[0036] The number average molecular weight Mn of poly(4,5-diazadibenzofulvene) is preferably 800 to 2400, more preferably 1000 to 2000, still more preferably 1400 to 1800, and particularly preferably 1600. When the number average molecular weight Mn of poly(4,5-diazadibenzofulvene) is within the above range, 4,5-diazadibenzofulvene groups are easily accumulated by π-π interactions, and proton conduction paths are easily generated, so that the proton conductivity of the proton conductive material is easily improved. Poly(4,5-diazadibenzofulvene) can be synthesized, for example, by referring to the 63rd Annual Meeting of the Polymer Society (Presentation No. 1Pa007).
[0037] As the proton channel polymer, polyalkylene oxides are also preferred from the viewpoint of improving the durability of the proton conductive material, and among these, polyethylene oxide is more preferred. It is preferable to use a proton channel polymer containing at least one group selected from the group consisting of a pyridyl group, a phenanthroline group, and a diazadibenzofulvene group in combination with a polyalkylene oxide, since this improves the proton conductivity of the proton conductive material while also improving its durability. A proton conductive material containing a polyalkylene oxide and thus improving its durability can provide a proton conductive membrane with excellent flexibility, and can be made thin and large in area. In addition, when the proton conducting material according to the first embodiment of the present disclosure contains, as a proton source polymer, a polymer that forms a layered structure due to π-π interaction, the proton channel polymer may contain only polyalkylene oxide.
[0038] The number average molecular weight Mn of the polyethylene oxide is not particularly limited, but is preferably 300 to 600000, more preferably 500 to 550000, and even more preferably 600 to 510000. When the number average molecular weight Mn of the polyethylene oxide is equal to or more than the above lower limit, it is effective in improving the durability of the proton conductive material, and when it is equal to or less than the above upper limit, it suppresses the decrease in the proton conductivity of the proton conductive material.
[0039] In the first embodiment of the present disclosure, among the combinations of the proton source polymer and the proton channel polymer, preferred combinations that realize particularly high proton conductivity include, for example, a combination containing a styrenesulfonic acid-based polymer as the proton source polymer and poly(4,5-diazadibenzofulvene) as the proton channel polymer, a combination containing a styrenesulfonic acid-based polymer as the proton source polymer and poly(2-vinylpyridine) as the proton channel polymer, a combination containing a styrenesulfonic acid-based polymer as the proton source polymer and poly(1,10-phenanthroline) having a number average molecular weight Mn of 900 to 1100 as the proton channel polymer, and a combination containing a perfluorosulfonic acid-based polymer as the proton channel polymer and poly(1,10-phenanthroline) having a number average molecular weight Mn of 9000 to 11000 as the proton channel polymer. Among these, a combination containing a styrene sulfonic acid polymer as the proton source polymer and poly(4,5-diazadibenzofulvene) as the proton channel polymer is preferred because it has particularly high proton conductivity at high temperatures. In addition, in terms of high proton conductivity and excellent durability, a combination containing polyethylene oxide as a proton polymer channel is also preferred in addition to the above-mentioned preferred combinations. Among them, in terms of particularly high proton conductivity at high temperatures and high proton conductivity and excellent durability, a combination containing a styrenesulfonic acid polymer as a proton source polymer and poly(4,5-diazadibenzofulvene) and polyethylene oxide as proton channel polymers is preferred.
[0040] In the first embodiment of the present disclosure, the mass ratio of the proton source polymer to the proton channel polymer is appropriately adjusted so as to improve the proton conductivity depending on the type of each polymer, and is not particularly limited, but the content of the proton channel polymer relative to 100 parts by mass of the proton source polymer is usually 1 to 15 parts by mass, and preferably 2 to 10 parts by mass. When the content of the proton channel polymer relative to the proton source polymer is within the above range, the conformation is likely to be such that a proton conductive path is easily formed between the proton source group and the proton channel, and therefore the proton conductivity is likely to be improved. In particular, in the case of a combination containing a styrenesulfonic acid-based polymer as the proton source polymer and poly(4,5-diazadibenzofulvene) as the proton channel polymer, the content of poly(4,5-diazadibenzofulvene) relative to 100 parts by mass of the styrenesulfonic acid-based polymer is preferably 1 to 15 parts by mass, more preferably 3 to 10 parts by mass. In the case of a combination containing a styrenesulfonic acid polymer as a proton source polymer, poly(4,5-diazadibenzofulvene) as a proton channel polymer, and further containing polyethylene oxide, the content of poly(4,5-diazadibenzofulvene) is preferably 1 to 5 parts by mass, more preferably 2 to 4 parts by mass, and even more preferably 3 parts by mass, and the content of polyethylene oxide is preferably 8 to 12 parts by mass, more preferably 9 to 11 parts by mass, and even more preferably 10 parts by mass, relative to 100 parts by mass of the styrenesulfonic acid polymer. In the case of a combination containing a styrene sulfonic acid polymer as the proton source polymer and poly(2-vinylpyridine) as the proton channel polymer, the content of poly(2-vinylpyridine) relative to 100 parts by mass of the styrene sulfonic acid polymer is preferably 8 to 12 parts by mass, more preferably 9 to 11 parts by mass, and even more preferably 10 parts by mass. In the case of a combination containing a styrenesulfonic acid polymer as the proton source polymer and poly(1,10-phenanthroline) having a number average molecular weight Mn of 900 to 1100 as the proton channel polymer, the content of poly(1,10-phenanthroline) relative to 100 parts by mass of the styrenesulfonic acid polymer is preferably 1 to 5 parts by mass, more preferably 1 to 3 parts by mass, and even more preferably 2 parts by mass. In the case of a combination containing a perfluorosulfonic acid polymer as the proton channel polymer and poly(1,10-phenanthroline) having a number average molecular weight Mn of 9000 to 11000 as the proton channel polymer, the content of poly(1,10-phenanthroline) relative to 100 parts by mass of the perfluorosulfonic acid polymer is preferably 8 to 12 parts by mass, more preferably 9 to 11 parts by mass, and even more preferably 10 parts by mass. In the case of a combination containing at least one selected from a styrenesulfonic acid-based polymer and a perfluorosulfonic acid-based polymer as a proton source polymer, containing at least one selected from poly(2-vinylpyridine) and poly(1,10-phenanthroline) as a proton channel polymer, and further containing polyethylene oxide, the content of polyethylene oxide relative to 100 parts by mass of the styrenesulfonic acid-based polymer is preferably 8 to 12 parts by mass, more preferably 9 to 11 parts by mass, and even more preferably 10 parts by mass.
[0041] (Physical Properties) The proton conducting material according to the first embodiment of the present disclosure has a structure in which at least a portion of a polymer containing an aromatic ring is laminated through π-π interactions. The polymer in the proton conductive material has a structure in which the polymer is stacked by π-π interactions, for example,1 The degree of the cleavage can be confirmed by H-NMR spectroscopy or ultraviolet absorption spectroscopy. Specifically, the method described in T. Nakano and T. Yade, Journal of the American Chemical Society, 2003, 125, p. 15474-15484 can be adopted. In the proton conducting material according to the first embodiment of the present disclosure, by containing at least one of the proton source polymers and proton channel polymers described above that contain aromatic rings and are likely to form a stacked structure through π-π interactions, it is possible to provide a proton conducting material in which at least a portion of the polymer containing an aromatic ring has a stacked structure through π-π interactions.
[0042] The proton conductive material according to the first embodiment of the present disclosure can have a proton conductivity in the film thickness direction of the proton conductive material formed into a film at 25° C. under unhumidified conditions of 10 mS / cm or more, preferably 20 mS / cm or more, and more preferably 30 mS / cm or more.
[0043] The form of the proton conductive material according to the first embodiment of the present disclosure is not particularly limited, and may be, for example, a membrane, that is, a proton conductive membrane. The proton conductive membrane can be used, for example, as a solid electrolyte membrane of a fuel cell. The thickness of the proton conductive membrane is appropriately adjusted depending on the application and is not particularly limited, but can be, for example, 0.1 to 5.0 mm.
[0044] (Manufacturing method) The method for producing the proton conductive material according to the first embodiment of the present disclosure is not particularly limited as long as it is a method that can obtain the above-mentioned proton conductive material. For example, the proton conductive material according to the first embodiment of the present disclosure can be produced by a method that includes a step of obtaining a mixed solution containing a proton source polymer, a proton channel polymer, and a solvent, and a step of removing the solvent from the mixed solution.
[0045] The solvent used in the mixed solution is appropriately selected according to the type of polymer, and is not particularly limited, and for example, water, an organic solvent, or a mixed solvent thereof can be used. The mixed solution can be obtained, for example, by mixing a solution in which a proton source polymer is dissolved in a solvent with a solution in which a proton channel polymer is dissolved in a solvent. In this case, it is preferable to select a solvent so that these solutions are mixed uniformly, and for example, water, alcohol, or a mixed solvent thereof can be preferably used. As the alcohol, methanol is typically used.
[0046] When the proton conductive material is to be formed into a membrane, in the step of removing the solvent from the mixed liquid, the mixed liquid is dried into a membrane by, for example, a drop casting method, whereby a membrane-shaped proton conductive material can be produced. The method for removing the solvent from the above-mentioned mixed liquid is not particularly limited, and the solvent may be removed, for example, by drying in an air atmosphere at room temperature or on a hot plate at, for example, 60°C.
[0047] Second Embodiment A proton conductive material according to a second embodiment of the present disclosure contains a proton source crosslinked polymer, the proton source crosslinked polymer being a polymer having a main skeleton including a proton source group and an aromatic ring, and a crosslinked structure including a proton channel, and at least a portion of the proton source crosslinked polymer has a structure stacked by π-π interactions. The above-mentioned proton source crosslinked polymer has a main skeleton containing a proton source group and an aromatic ring, which is crosslinked by a crosslinking structure containing a proton channel, and has a three-dimensional structure, and is therefore presumably likely to form a layered structure through π-π interactions. As described above, the proton conductive material according to the second embodiment of the present disclosure has high proton conductivity even in the absence of humidity. In addition, the proton conductive material according to the second embodiment of the present disclosure can maintain excellent durability because the proton source crosslinked polymer has a crosslinked structure. Therefore, the proton conductive material according to the second embodiment of the present disclosure has high proton conductivity and excellent durability, and deterioration over time is suppressed, so that a proton conductive membrane that can maintain high proton conductivity for a long period of time can be provided. In addition, the proton conductive material according to the second embodiment of the present disclosure has excellent flexibility, so that a proton conductive membrane can be made thin and large in area.
[0048] (Proton Source Cross-Linked Polymer) The proton source crosslinked polymer used in the second embodiment of the present disclosure is a polymer having a main skeleton, which is a polymer skeleton containing a proton source group and an aromatic ring, and a crosslinked structure containing a proton channel, and may be a hydrocarbon-based organic polymer. The proton source group is the same as that in the first embodiment described above, and the proton source group preferred in the first embodiment is also preferred in the second embodiment.
[0049] In order to improve the proton conductivity of the proton conductive material, the proton source crosslinked polymer may have a polymer skeleton in which the main skeleton is composed of structural units derived from a monomer containing a proton source group, and the content of structural units derived from a monomer containing a proton source group is preferably 90 parts by mass or more, and more preferably 95 parts by mass or more, out of 100 parts by mass of all structural units of the main skeleton. Furthermore, since the above-mentioned proton source crosslinked polymer is likely to form a stacked structure through π-π interactions and the proton conductivity of the proton conductive material is likely to be improved, the content of constituent units derived from a monomer containing a proton source group and an aromatic ring is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, out of 100 parts by mass of all constituent units of the main skeleton, and the main skeleton may be a polymer skeleton consisting of constituent units derived from a monomer containing a proton source group and an aromatic ring. In the second embodiment of the present disclosure, the mass of the main skeleton and the mass of the crosslinked structure in the proton source crosslinked polymer are the mass of the structure derived from the compound forming the main skeleton and the mass of the structure derived from the compound forming the crosslinked structure, respectively, and can be calculated from the masses of the compounds used in synthesizing the polymer.
[0050] In the above-mentioned proton source crosslinked polymer, examples of the constituent units derived from monomers containing a proton source group and an aromatic ring and contained in the main skeleton include constituent units derived from monomers such as 4-styrenesulfonic acid, 4-vinylbenzoic acid, 2-vinylbenzoic acid, 4-vinylphenol, 2-vinylphenol, 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole, 4-(1H-imidazol-1-yl)styrene, 2-vinyl-1H-benzimidazole, and 1-vinyl-1H-benzimidazole. Among them, a main skeleton derived from a styrene sulfonic acid-based polymer is preferred because it is easy to form a laminated structure by π-π interactions and to improve the proton conductivity of the proton-conducting material. With respect to the styrene sulfonic acid-based polymer serving as the main skeleton in the second embodiment, preferred aspects such as the content of structural units derived from styrene sulfonic acid and the number average molecular weight are the same as those of the styrene sulfonic acid-based polymer used in the above-mentioned first embodiment.
[0051] The crosslinked structure of the proton source crosslinked polymer is a crosslinked structure containing a proton channel. The crosslinked structure may be a crosslinked structure formed by a covalent bond, a crosslinked structure formed by an intermolecular force other than a covalent bond, or a crosslinked structure formed by a known crosslinking agent. Examples of the intermolecular force other than a covalent bond include van der Waals force, charge transfer force, Coulomb force, hydrophobic bond force, hydrogen bond force, ionic bond force, coordinate bond force, or a combination thereof. Examples of the structure that serves as the proton channel contained in the crosslinked structure include those similar to those described in the first embodiment above, and among them, at least one selected from a primary or secondary amino group, an amide group, and an amide bond is preferable.
[0052] The crosslinked structure may be formed by a crosslinking agent containing a proton channel. The crosslinking agent used to form the crosslinked structure may contain at least one structure that serves as a proton channel, but from the viewpoint of improving the proton conductivity, it is preferable that the crosslinking agent contains two or more structures that serve as proton channels, and more preferably contains two structures that serve as proton channels.
[0053] The crosslinked structure formed by a covalent bond is not particularly limited, but for example, a crosslinked structure formed by a crosslinking agent such as N,N'-methylenebisacrylamide can be preferably used. The crosslinked structure formed by a covalent bond can be formed by copolymerizing a monomer or macromonomer forming the main skeleton with a crosslinking agent. The copolymer obtained by the copolymerization may be any of a random copolymer, a block copolymer, and a graft copolymer, but a random copolymer is preferred from the viewpoint of improving the proton conductivity.
[0054] In addition, when a water-soluble crosslinking agent such as N,N'-methylenebisacrylamide is used as the crosslinking agent for forming the crosslinked structure, for example, a salt such as sodium styrenesulfonate and the water-soluble crosslinking agent are copolymerized in water, followed by hydrogenation, to obtain a proton source crosslinked polymer in which a crosslinked structure derived from the water-soluble crosslinking agent is introduced into a main skeleton derived from a styrenesulfonic acid polymer. Sodium styrenesulfonate has a higher polymerizability than styrenesulfonic acid, so that a main skeleton of a desired molecular weight can be easily formed by carrying out a polymerization reaction using sodium styrenesulfonate. Among the water-soluble crosslinking agents, N,N'-methylenebisacrylamide is particularly preferred since it is likely to improve the proton conductivity and durability of the proton-conducting material.
[0055] Among the crosslinked structures formed by intermolecular forces other than covalent bonds, crosslinked structures formed by hydrogen bonding forces are preferred. Examples of crosslinked structures that include proton channels and are formed by hydrogen bonding forces include crosslinked structures derived from diamino compounds such as alkylenediamines having an alkylene group with 1 to 6 carbon atoms, such as 1,6-diaminohexane (DAH) and 1,2-diaminoethane (DAE). Crosslinked structures derived from diamino compounds can be formed, for example, by mixing a polymer that serves as the main skeleton with a diamino compound in a solution.
[0056] The molecular weight of the crosslinking agent used to form the crosslinked structure is not particularly limited, but is preferably 30 to 300, more preferably 50 to 200, and even more preferably 60 to 160, from the viewpoint of easily improving the proton conductivity and durability of the proton conductive material.
[0057] In addition, the crosslinked structure preferably has proton channels at both ends of the linear alkylene group, from the viewpoint of easily improving the proton conductivity and durability of the proton-conductive material. The linear alkylene group preferably has 1-10 carbon atoms, and more preferably 1-6 carbon atoms.
[0058] As the proton source crosslinked polymer, from the viewpoint of obtaining a proton conductive material having high proton conductivity and excellent durability, a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from N,N'-methylenebisacrylamide, a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from 1,6-diaminohexane, and a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from 1,2-diaminoethane are preferred. Among them, from the viewpoint of obtaining a particularly high proton conductivity in a wide temperature range, a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from N,N'-methylenebisacrylamide is more preferred.
[0059] In the above-mentioned proton source crosslinked polymer, the content of the crosslinked structure is appropriately adjusted so as to improve the proton conductivity of the proton conductive material, and is not particularly limited, but is usually 1 to 15 parts by mass, and preferably 1 to 10 parts by mass, per 100 parts by mass of the main skeleton. When the content of the crosslinked structure including a proton channel relative to the main skeleton including a proton source group and an aromatic ring is within the above range, the conformation is likely to be such that a proton conduction path is likely to be formed between the proton source group and the proton channel, and therefore the proton conductivity is likely to be improved. In particular, in a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from N,N'-methylenebisacrylamide, the content of the crosslinked structure relative to 100 parts by mass of the main skeleton is preferably 1 to 7 parts by mass, more preferably 1 to 5 parts by mass. In the case of a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from 1,6-diaminohexane, the amount is preferably 1 to 7 parts by mass, and more preferably 1 to 5 parts by mass. In the case of a polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from 1,2-diaminoethane, the amount is preferably 1 to 7 parts by mass, and more preferably 3 to 5 parts by mass.
[0060] (Proton channel polymer) The proton conductive material according to the second embodiment of the present disclosure may further contain a proton channel polymer. The proton channel polymer used in the second embodiment preferably does not contain a proton source group. Examples of the proton channel polymer used in the second embodiment include the same proton channel polymer as that used in the first embodiment described above. As the proton channel polymer used in the second embodiment, at least one selected from the group consisting of poly(2-vinylpyridine), poly(1,10-phenanthroline) and poly(4,5-diazadibenzofulvene) is preferable, and poly(4,5-diazadibenzofulvene) is more preferable. In the second embodiment, the preferred number average molecular weights Mn of poly(2-vinylpyridine), poly(1,10-phenanthroline) and poly(4,5-diazadibenzofulvene) are the same as those in the first embodiment described above. When the proton conductive material according to the second embodiment of the present disclosure further contains a proton channel polymer, the content of the proton channel polymer is usually 1 to 10 parts by mass, and preferably 1 to 5 parts by mass, per 100 parts by mass of the main skeleton including the above-mentioned proton source group and aromatic ring.
[0061] (Physical Properties) The proton conductive material according to the second embodiment of the present disclosure has a structure in which at least a part of the proton source crosslinked polymer is laminated by π-π interaction. The fact that the polymer in the proton conductive material has a structure in which the polymer is laminated by π-π interaction can be confirmed by the same method as in the first embodiment described above.
[0062] In the proton conductive material according to the second embodiment of the present disclosure, the proton conductivity in the film thickness direction of the proton conductive material formed into a film at 25° C. and in an unhumidified state can be 10 mS / cm or more, preferably 20 mS / cm or more, and more preferably 30 mS / cm or more.
[0063] The form of the proton-conducting material according to the second embodiment of the present disclosure is similar to that of the first embodiment described above.
[0064] (Manufacturing method) The method for producing the proton conductive material according to the second embodiment of the present disclosure is not particularly limited as long as it is a method that can obtain the above-mentioned proton conductive material. As a method for producing a proton conductive material containing a polymer having a main skeleton containing a proton source group and an aromatic ring, and a crosslinked structure containing a proton channel and formed by a covalent bond, as a proton source crosslinked polymer, there can be mentioned, for example, a method in which a monomer or macromonomer forming the main skeleton is copolymerized with a crosslinking agent, and then hydrogenated as necessary to obtain a proton source crosslinked polymer, and the obtained proton source crosslinked polymer is molded into a desired shape. The copolymerization may be any of random copolymerization, block copolymerization and graft copolymerization, but random copolymerization is preferred since it is easy to obtain a proton source crosslinked polymer having high proton conductivity.
[0065] Examples of methods for producing a proton conductive material containing a proton source crosslinked polymer having a main skeleton containing a proton source group and an aromatic ring, and a polymer having a crosslinked structure containing a proton channel and formed by an intermolecular force other than a covalent bond include a method of adding a crosslinking agent that forms the crosslinked structure to a solution in which the main skeleton polymer is dissolved, and mixing to obtain a proton source crosslinked polymer, preparing a mixed solution containing the obtained proton source crosslinked polymer, a proton channel polymer that is added as necessary, and a solvent, and removing the solvent from the mixed solution. Here, the mixed liquid may be a solution in which only the proton source crosslinked polymer is dissolved in a solvent. The solvent used in the above-mentioned mixed solution is appropriately selected according to the type of polymer or crosslinking agent, and is not particularly limited, and for example, water, an organic solvent, or a mixed solvent thereof can be used. The above-mentioned mixed solution can be obtained, for example, by mixing a solution in which a proton source crosslinked polymer is dissolved in a solvent with a solution in which a proton channel polymer is dissolved in a solvent. In that case, it is preferable to select a solvent so that these solutions are mixed uniformly, and for example, water, alcohol, or a mixed solvent thereof can be preferably used. As the alcohol, methanol is typically used. The method for removing the solvent from the mixed liquid and the method for forming the mixed liquid into a membrane are the same as those in the method for producing the proton-conductive material according to the first embodiment described above. EXAMPLES
[0066] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to these examples. It should be noted that Examples 11 to 17 shown in the following Table 3 are reference examples. The thickness of the proton conductive membrane obtained in each Example and the comparative conductive membrane obtained in each Comparative Example was measured using a micrometer (manufactured by Mitutoyo Corp., model number: CLM1-15QM).
[0067] [Comparative Example 1] A solution of polystyrene sulfonic acid (Mn7000) was drop cast onto a steel electrode having a diameter of 5 mm to form a film, thereby obtaining a comparative conductive membrane of Comparative Example 1 having a thickness shown in Table 1.
[0068] [Example 1] A mixed solution was obtained by mixing a water-alcohol solution in which polystyrene sulfonic acid (Mn 7000) was dissolved and a methanol solution in which poly(4,5-diazadibenzofulvene) (Mn 1600) was dissolved in such amounts that the mass ratio of polystyrene sulfonic acid to poly(4,5-diazadibenzofulvene) was the value shown in Table 1. The resulting mixed solution was drop-cast onto a steel electrode with a diameter of 5 mm to form a membrane, thereby obtaining a proton conductive membrane of Example 1 having a thickness shown in Table 1.
[0069] [Examples 2 to 5] The proton conductive membranes of Examples 2 to 5 were obtained in the same manner as in Example 1, except that in Example 1, the proton channel polymer shown in Table 1 was used instead of poly(4,5-diazadibenzofulvene), and the amount of each solution added was changed as necessary so that the mass ratio of polystyrene sulfonic acid to the proton channel polymer was the value shown in Table 1.
[0070] [Comparative Example 2] A Nafion membrane (product name: NR212, manufactured by Chemours, membrane thickness 0.31 mm) made of perfluorosulfonic acid resin was used as the comparative conductive membrane in Comparative Example 2.
[0071] [Example 6] A mixture was obtained by mixing a suspension of Nafion and a water-alcohol solution in which poly(1,10-phenanthroline) (Mn 10000) was dissolved in such amounts that the mass ratio of Nafion to poly(1,10-phenanthroline) was the value shown in Table 1. Using the mixture obtained, a proton conductive membrane of Example 6 having a thickness shown in Table 1 was obtained by the same method as in Example 1.
[0072] [Example 7] A mixed solution was obtained by mixing a water-alcohol solution in which polystyrene sulfonic acid (Mn7000) was dissolved, a methanol solution in which poly(4,5-diazadibenzofulvene) (Mn1600) was dissolved, and a methanol solution in which polyethylene oxide (Mn600) was dissolved, in amounts such that the mass ratio of polystyrene sulfonic acid to poly(4,5-diazadibenzofulvene) to polyethylene oxide was the value shown in Table 2. Using the obtained mixed solution, a proton conductive membrane of Example 7 having a thickness shown in Table 2 was obtained by the same method as in Example 1.
[0073] [Examples 8 to 10] Proton conductive membranes of Examples 8 to 10 were obtained in the same manner as in Example 7, except that polyethylene oxides having number average molecular weights shown in Table 2 were used instead of the polyethylene oxide (Mn600) in Example 7.
[0074] [Example 11] A mixed solution was obtained by adding 1,6-diaminohexane to a water-alcohol solution in which polystyrene sulfonic acid (Mn7000) was dissolved, in an amount such that the mass ratio of polystyrene sulfonic acid to 1,6-diaminohexane was the value shown in Table 3. Using the obtained mixed solution, a proton conductive membrane of Example 11 having a thickness shown in Table 3 was obtained by the same method as in Example 1.
[0075] [Examples 12 to 13] Proton conductive membranes of Examples 12 to 13 were obtained in the same manner as in Example 11, except that the amount of 1,6-diaminohexane added was changed so that the mass ratio of polystyrene sulfonic acid to 1,6-diaminohexane in Example 11 was the value shown in Table 3.
[0076] [Example 14] A mixed solution was obtained by mixing a water-alcohol solution in which polystyrene sulfonic acid (Mn7000) was dissolved, and a methanol solution in which poly(4,5-diazadibenzofulvene) (Mn1600) and 1,6-diaminohexane were dissolved, in amounts such that the mass ratio of polystyrene sulfonic acid to poly(4,5-diazadibenzofulvene) to 1,6-diaminohexane was the value shown in Table 3. Using the obtained mixed solution, a proton conductive membrane of Example 14 having a thickness shown in Table 3 was obtained by the same method as in Example 1.
[0077] [Examples 15 to 16] Proton conductive membranes of Examples 15 and 16 were obtained in the same manner as in Examples 12 and 13, except that 1,2-diaminoethane was used instead of 1,6-diaminohexane.
[0078] [Example 17] A proton conductive membrane of Example 17 was obtained in the same manner as in Example 14, except that 1,2-diaminoethane was used instead of 1,6-diaminohexane.
[0079] [Example 18] The proton conductive membrane of Example 18 was obtained by adjusting the amount of N,N'-methylenebisacrylamide (MBAA) added in the following scheme 1 to be 1 part by mass per 100 parts by mass of polystyrene sulfonic acid. That is, N,N'-methylenebisacrylamide was added to a 2 mol / L (2M) aqueous solution of sodium 4-styrenesulfonate, and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] was further added as a water-soluble initiator, and the mixture was reacted at 86°C to obtain a random copolymer gel of sodium 4-styrenesulfonate and N,N'-methylenebisacrylamide. The obtained copolymer gel was immersed in 3M hydrochloric acid, washed with water, and vacuum dried for 24 hours to obtain the proton conductive membrane of Example 18.
[0080] [ka]
[0081] [Example 19] A proton conductive membrane of Example 19 was obtained in the same manner as in Example 18, except that the amount of N,N'-methylenebisacrylamide added was changed to 5 parts by mass per 100 parts by mass of polystyrene sulfonic acid.
[0082] [evaluation] <Measurement of proton conductivity> The conductivity measurement cell was placed in the tank of a small environmental tester (manufactured by Espec Corp., model: SH-242), and the characteristic impedance was measured using an impedance analyzer (manufactured by YHP Corp., model: 4194A) at the temperatures and non-humidified conditions shown in Tables 1 to 4 or Figure 1, with a frequency sweep range of 100 Hz to 1 MHz. The real component of the point where the capacitance component of the Nyquist plot of the characteristic impedance is minimum was taken as the measured value (Rm), and the conductivity (σ) (unit: S / cm) in the film thickness direction was calculated according to the following formula using the film thickness (d) and electrode area (S) of the sample as the impedance characteristic (Ru) when the measurement cable was shorted. σ=d / {(Rm-Ru)×S}
[0083] <Durability> The proton conductive membranes obtained in Examples 1, 2, and 7 to 19 were visually observed when heated to 110° C. and when stored at room temperature for a long period of time, and the durability of the proton conductive membranes was evaluated according to the following evaluation criteria. (Durability evaluation criteria) A: The film does not collapse after heating or after long-term storage at room temperature. B: The membrane does not collapse after short-term storage at room temperature, but collapses after heating or long-term storage at room temperature. C: The membrane collapses after short storage at room temperature.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] [Table 4]
[0088] The abbreviations in Tables 1 to 4 are as follows. PSS: Polystyrene sulfonate (Mn7000) Nafion: Nafion (registered trademark) (product number: NR212, manufactured by DuPont) Poly(DADBF): Poly(4,5-diazadibenzofulvene) (Mn1600) Poly(2VPy)500: Poly(2-vinylpyridine) (Mn500) Poly(Phen)1000: Poly(1,10-phenanthroline) (Mn1000) Poly(Phen)10000: Poly(1,10-phenanthroline) (Mn10000) PEO600: Polyethylene oxide (Mn600) PEO3000: Polyethylene oxide (Mn3000) PEO46000: Polyethylene oxide (Mn46000) PEO510000: Polyethylene oxide (Mn510000) DAH: 1,6-diaminohexane DAE: 1,2-diaminoethane MBAA: N,N'-methylenebisacrylamide
[0089] <Water resistance> The water resistance of the proton conductive membrane obtained in Example 18 was evaluated by the following methods A and B.
[0090] (Method A) A sample was prepared by cutting out about 100 mg of the proton conductive membrane obtained in Example 18. The sample was weighed to be 92.85 mg. The sample was immersed in water at 80°C for 1 hour, air-dried for 4 days, and further vacuum-dried for 24 hours. The sample was weighed to be 90.14 mg, and a weight loss of 2.9% (2.71 mg) was observed. The weight loss is sufficiently small compared to that of conventional proton conductive membranes, and is considered to be due to insufficient drying of the measurement sample or an error due to mechanical loss etc. resulting from a small-scale experiment. Therefore, it was clarified that the proton conductive membrane obtained in Example 18 has high water resistance and is not dissolved in water.
[0091] (Method B) A sample was prepared by cutting out the proton conductive membrane obtained in Example 18. The sample was immersed in water at room temperature (25°C) for 24 hours to cause swelling, and the sample after swelling was weighed to be 6160 mg. The swollen sample was further immersed in water at 80°C for 1 hour and weighed to be 6950 mg, and a weight increase of 12.8% (790 mg) was observed. The weight increase is presumably due to insufficient swelling of the sample before it was immersed in water at 80° C. Therefore, it was clarified that the proton conductive membrane obtained in Example 18 has high water resistance such that it is not dissolved in water even after it is sufficiently swollen with water.
[0092] The results of measuring the proton conductivity of the proton conductive membrane obtained in Example 18 at temperatures ranging from -20°C to 150°C under unhumidified conditions at 5% RH, and the results of measuring the proton conductivity of the comparative conductive membrane of Comparative Example 2 at temperatures ranging from -20°C to 150°C under unhumidified conditions at 5% RH, are shown in Figure 1. In Figure 1, the horizontal axis is 1000 / T (T is the measurement temperature (K)), and the vertical axis is proton conductivity (S / cm).
[0093] The proton conductive membranes obtained in Examples 1 to 10 shown in Tables 1 and 2 are proton conductive materials according to the first embodiment of the present disclosure, and contain polystyrene sulfonic acid or Nafion (registered trademark) as a proton source polymer, and poly(4,5-diazadibenzofulvene), poly(2-vinylpyridine) or poly(1,10-phenanthroline) as a proton channel polymer. These proton channel polymers have proton channels containing aromatic rings that are likely to form a layered structure through π-π interactions, and therefore the proton conductive membranes obtained in Examples 1 to 10 have a structure in which at least a portion of the proton channel polymer is layered through π-π interactions. The proton conductive membranes obtained in Examples 1 to 10, which are proton conductive materials according to the first embodiment of the present disclosure, had high proton conductivity of 10 mS / cm or more at 25° C. under unhumidified conditions, and had improved proton conductivity compared to the polystyrene sulfonic acid membrane of Comparative Example 1 and the Nafion membrane of Comparative Example 2. Furthermore, in the proton conductive membranes obtained in Examples 1 to 10, the proton source groups and proton channels were covalently bonded to the polymer and therefore did not dissolve in water, and therefore the proton conductive membranes obtained in Examples 1 to 10 did not contain any components that would dissolve in water.
[0094] Moreover, in Example 2 shown in Table 1, it was shown that the proton conducting material according to the first embodiment of the present disclosure, which contains a styrene sulfonate-based polymer as a proton source polymer and poly(4,5-diazadibenzofulvene) as a proton channel polymer, has extremely high proton conductivity even at high temperatures and in the absence of humidity. A comparison of Examples 1-2 and Examples 7-10 shown in Table 2 indicates that the proton conducting material according to the first embodiment of the present disclosure, which further contains polyethylene oxide as a proton channel polymer, exhibits improved durability while suppressing a decrease in proton conductivity.
[0095] The proton conductive membranes obtained in Examples 11 to 19 shown in Tables 3 and 4 are proton conductive materials according to the second embodiment of the present disclosure, and have a main skeleton derived from polystyrene sulfonic acid as a main skeleton containing a proton source group and an aromatic ring, and contain a proton source crosslinked polymer having a crosslinked structure derived from 1,6-diaminohexane, 1,2-diaminoethane, or N,N'-methylenebisacrylamide as a crosslinked structure containing a proton channel, and at least a portion of the proton source crosslinked polymer has a structure stacked by π-π interactions. The proton conductive membranes obtained in Examples 11 to 19, which are proton conductive materials according to the second embodiment of the present disclosure, also had high proton conductivity of 10 mS / cm or more at 25° C. under unhumidified conditions, and had improved proton conductivity compared to the polystyrene sulfonic acid membrane of Comparative Example 1 and the Nafion membrane of Comparative Example 2. Furthermore, in the proton conductive membranes obtained in Examples 11 to 19, the proton source groups were bonded to the main skeleton by covalent bonds, the proton channels were bonded to the crosslinked structure or the proton channel polymer by covalent bonds, and the crosslinked structure was chemically bonded to the main skeleton, so that the proton source groups and the proton channels were not dissolved in water, and the proton conductive membranes obtained in Examples 11 to 19 did not contain any components that would dissolve in water. Moreover, the proton conductive membranes obtained in Examples 11 to 19 had high proton conductivity and excellent durability.
[0096] In addition, in Example 18 shown in Table 4, it was shown that the proton conductive material according to the second embodiment of the present disclosure, which contains a proton source crosslinked polymer having a main skeleton derived from a styrenesulfonic acid polymer and a crosslinked structure derived from N,N'-methylenebisacrylamide, has high proton conductivity even at high temperatures and in a non-humidified state, and is also excellent in durability. In addition, it was confirmed that the proton conductive membrane obtained in Example 18 showed almost no change even after storage at room temperature for 3 days, and deterioration over time was suppressed. Furthermore, the proton conductive membrane obtained in Example 18 was evaluated for water resistance as described above, and as a result, it was shown to have high water resistance. In addition, the results shown in FIG. 1 indicate that the proton conductive membrane obtained in Example 18 has high proton conductivity in a wide temperature range and in an unhumidified environment. In addition, since the comparative conductive membrane of Comparative Example 2 is a Nafion membrane, the proton conductivity was insufficient under non-humidified conditions. In the comparative conductive membrane of Comparative Example 2, the proton conductivity increased with increasing temperature as shown in FIG. 1. This is presumably because the glass transition temperature of the Nafion membrane of Comparative Example 2 is 109°C, which improves molecular mobility. In addition, it is possible that trace amounts of moisture were not completely removed, and that the membrane thickness became thinner at high temperatures, which reduced resistance, resulting in an increase in apparent proton conductivity. In the measurement cell to which surface pressure was applied, the membrane may have softened at high temperatures, reducing the membrane thickness.
[0097] Thus, the proton conductive material of the present disclosure is a proton conductive material that has high proton conductivity even under non-humidified conditions and is not dissolved in water, and can be suitably used as an electrolyte material for a catalyst layer used in a fuel cell or a solid electrolyte membrane used in a fuel cell.
Claims
1. A proton conducting material (excluding those containing an organic phosphorus compound) comprising a polymer containing a proton source group and a polymer containing a proton channel, wherein at least one selected from the group consisting of the polymer containing the proton source group and the polymer containing the proton channel is a polymer containing an aromatic ring, and at least a part of the polymer containing an aromatic ring has a structure stacked by π-π interaction, A proton-conducting material having the following configuration (i), (ii), (iii) or (iv): (i) The polymer containing a proton source group includes a styrenesulfonic acid polymer, and the polymer containing a proton channel includes poly(4,5-diazadibenzofulvene) having a number average molecular weight Mn of 1000 to 2000 in an amount of 1 to 15 parts by mass relative to 100 parts by mass of the styrenesulfonic acid polymer. (ii) The polymer containing a proton source group includes a styrene sulfonic acid polymer, and the polymer containing a proton channel includes poly(2-vinylpyridine) having a number average molecular weight Mn of 500 to 2000 in an amount of 8 to 12 parts by mass per 100 parts by mass of the styrene sulfonic acid polymer. (iii) The polymer containing a proton source group includes a styrene sulfonic acid polymer, and the polymer containing a proton channel includes poly(1,10-phenanthroline) having a number average molecular weight Mn of 900 to 1100 in an amount of 1 to 3 parts by mass per 100 parts by mass of the styrene sulfonic acid polymer. (iv) The polymer containing a proton source group includes a perfluorosulfonic acid polymer, and the polymer containing a proton channel includes poly(1,10-phenanthroline) having a number average molecular weight Mn of 9,000 to 11,000 in an amount of 8 to 12 parts by mass per 100 parts by mass of the perfluorosulfonic acid polymer.
2. The proton conducting material according to claim 1 , further comprising polyethylene oxide as the polymer containing the proton channel.
3. Having the configuration of (i), 2. The proton conductive material according to claim 1, comprising 1 to 5 parts by mass of poly(4,5-diazadibenzofulvene) having a number average molecular weight Mn of 1000 to 2000 relative to 100 parts by mass of the styrenesulfonic acid-based polymer, and further comprising 8 to 12 parts by mass of polyethylene oxide having a number average molecular weight Mn of 600 to 510,000 relative to 100 parts by mass of the styrenesulfonic acid-based polymer.
4. The polymer includes a proton source group and a proton channel, the polymer including a proton source group and a proton channel has a main skeleton including a proton source group and an aromatic ring, and a crosslinked structure including a proton channel; the main skeleton is derived from a styrene sulfonic acid-based polymer, and the content of the structural units derived from styrene sulfonic acid is 95 parts by mass or more in 100 parts by mass of all structural units of the styrene sulfonic acid-based polymer; the crosslinked structure is a crosslinked structure derived from N,N'-methylenebisacrylamide, The crosslinked structure is contained in an amount of 1 to 5 parts by mass relative to 100 parts by mass of the main skeleton, A proton conducting material having a structure in which at least a portion of the polymer containing the proton source group and the proton channel is laminated by π-π interaction.
5. The proton conducting material described in claim 4, wherein the styrene sulfonic acid-based polymer is polystyrene sulfonic acid composed of structural units derived from styrene sulfonic acid.
6. Further comprising a polymer containing a proton channel, 6. The proton conductive material according to claim 4, wherein the polymer containing the proton channel comprises a polymer containing at least one group selected from the group consisting of a pyridyl group, a phenanthroline group, and a diazadibenzofulvene group.
Citation Information
Patent Citations
Membrane-electrode joining body for solid polymer electrolyte fuel cell
JP2002246041A
Proton conductive polymeric solid electrolyte, its producing method, electrolytic membrane consisting thereof, its producing method, electrochemical element using electrolyte and / Or electrolytic membrane, and its producing method
JP2003242833A
Solid polyelectrolyte, its manufacturing method and solid polymer type fuel cell using it
JP2004335231A
Membrane electrode assembly, fuel cell stack, fuel cell system, and manufacturing method of membrane electrode assembly
JP2006032275A
Electrolyte membrane, manufacturing method of the same, membrane-electrode assembly, and fuel cell using the membrane-electrode assembly
JP2007179925A